REVITALISASI KAMPUNG IVA DI KELURAHAN BANDAR LOR WILAYAH KERJA PUSKESMAS SUKORAME - Pratamaningtyas, Susanti; Indrani, Ririn; Sendra, Eny (Politeknik Kesehatan Kemenkes malang, 2025)
Despite being preventable, cervical cancer is still considered the leading cause of death among women from developing countries. This cancer can be prevented by implementing early detection using the VIA method. The VIA village program, which was developed in 2020, is now revitalized with the same goal of reducing the incidence of cervical cancer. This time, the program will be implemented in Bandar Lor village, Kediri City which is included in the Sukorame Health Center area with 90 participants. Activities carried out include socialization, education and simultaneous VIA examinations. The team will also evaluate which parts are not yet understood by the community regarding early detection of cervical cancer through the IVA method, so that in the next program, more focused education can be carried out.